Projections of the Latin American archive in the journal Anclajes (Anclajes, 2021)
Throughout its issues, the journal Anclajes is presented as the ideal space for updating the agenda on Latin American literary studies and the archive. In its different facets, linked to the canon, tradition, the library, and characterized by its constitutive heterogeneity of materialities, technologies and supports, the Latin American archive has become a central problem and a critical perspective. This article traces its development throughout the history of the journal and analyzes the connection between the theoretical framework and the Latin American studies field.
Keywords: Latin American archive; academic production; academic journals; canon; heteronomy